Signs of Reincarnation: Exploring Beliefs, Cases, and Theory by James Matlock - Braude, Stephen (Journal of Scientific Exploration, 2021)
James Matlock’s book, Signs of Reincarnation, is a recent addition to a seemingly endless stream of confused or superficial works on the topic of survival. Admittedly (and as one would expect), the case material is often of genuine interest. But when Matlock tries to make sense of that material, he demonstrates little grasp of the current state of the debate. Even worse, he seems unaware of the intellectually responsible strategies for challenging and criticizing positions opposed to his own. Since Matlock criticizes what he says are my views throughout his book, and because this issue of the JSE features two comprehensive reviews of that book, I’ll focus only on the principal respects in which Matlock misdescribes my position and ignores the extended discussions I’ve provided, not only in Immortal Remains (Braude, 2003), but elsewhere (e.g., Braude, 2005a, 2005b, 2014a, 2014b, 2020), explaining the problems with the tired and flawed lines of reasoning he endorses.